2018
DOI: 10.1002/adma.201804691
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Strontium Doping and Chlorine Surface Passivation Improve Luminescence Intensity and Stability of CsPbI3 Nanocrystals Enabling Efficient Light‐Emitting Devices

Abstract: A method is proposed to improve the photo/electroluminescence efficiency and stability of CsPbI3 perovskite nanocrystals (NCs) by using SrCl2 as a co‐precursor. The SrCl2 is chosen as the dopant to synthesize the CsPbI3 NCs. Because the ion radius of Sr2+ (1.18 Å) is slightly smaller than that of Pb2+ (1.19 Å) ions, divalent Sr2+ cations can partly replace the Pb2+ ions in the lattice structure of perovskite NCs and cause a slight lattice contraction. At the same time, Cl− anions from SrCl2 are able to efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
227
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 246 publications
(235 citation statements)
references
References 38 publications
6
227
1
1
Order By: Relevance
“…), B site doping (with Mn 2+ , Ni 2+ , Sn 4+ , Ln 3+ , etc. ), surface engineering, matrix encapsulation, and postprocessing …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), B site doping (with Mn 2+ , Ni 2+ , Sn 4+ , Ln 3+ , etc. ), surface engineering, matrix encapsulation, and postprocessing …”
Section: Discussionmentioning
confidence: 99%
“…), 256 B site doping (with Mn 2+ , Ni 2+ , Sn 4+ , Ln 3+ , etc. ), [257][258][259][260][261][262][263][264] surface engineering, 195,197 matrix encapsulation, 196,265 and postprocessing. 161,266,267 Coupled with lattice incompleteness, many defects are presented in these NCs, including Schottky defects (cation and anion vacancies), Frenkel defects (interstitial sites), inversion defects, and structural defects (grain boundary, interface, and lattice distortion caused by impurities).…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously introducing Sr 2+ doping and Cl − surface passivation can also generate a high PLQY of 84 % (Table 1) for CsPbI 3 NCs with further enhanced materials stability. The resulting devices based on CsPbI 3 NCs with 10 % Sr 2+ substitution exhibit a much higher EQE of 13.5 % (Table 1) …”
Section: High‐performance Leds Based On Perovskite Ncs With Metal Dopmentioning
confidence: 99%
“…The divalent doping strategy of CsPbI 3 NCs can be combined with efficient halide surface passivation to further improve the material properties and the device performance. Yao et al [85] and Lu et al [86] independently demonstrated high performance red-emissive LEDs based on CsPbI 3 NCs with simultaneous strontium (Sr 2 + ) doping and iodide/chlorine surface passivation. Owing to the slightly smaller ion radius of Sr 2 + (118 pm) than the Pb 2 + (119 pm) ions, doping of the Sr 2 + into the CsPbI 3 NCs may cause a slight lattice contraction.…”
Section: Red-emissive Leds Based On Metal Doped/alloyed Perovskite Ncsmentioning
confidence: 99%
See 1 more Smart Citation